South Polar chart / from various authorities with amendments and additions to 1927 (Great Britain. Hydrographic Office, 1933)
Small corrections . 1933. Relief shown by spot heights and hachures. Depths shown by soundings.; "Engraved 1926."; "169.35" -- upper right margin. Color;